2017
DOI: 10.2147/dmso.s128502
|View full text |Cite
|
Sign up to set email alerts
|

Hearing thresholds in adult Nigerians with diabetes mellitus: a case–control study

Abstract: ObjectivesTo determine the prevalence, types and severity of hearing loss and associated factors in a hospital population of adult Nigerians with diabetes mellitus.Subjects and methodsThis study was a prospective hospital-based study conducted at the Otorhinolaryngology and Diabetic Clinics of the University of Nigeria Teaching Hospital (UNTH) Ituku-Ozalla, Enugu, for a period of 12 months. Consecutively presenting eligible adult diabetics and their age- and sex-matched healthy controls were recruited. Each ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…20,21 In the present study, the mean age of study participants was 52.13±13.31 years which was similar to earlier studies. [15][16][17] Similarly, female predominance in the current study was in line with existing studies. [20][21][22] Gyawali et al, 24 observed that type 2 diabetes mellitus exhibited pronounced excess of females in the Nepalese population.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…20,21 In the present study, the mean age of study participants was 52.13±13.31 years which was similar to earlier studies. [15][16][17] Similarly, female predominance in the current study was in line with existing studies. [20][21][22] Gyawali et al, 24 observed that type 2 diabetes mellitus exhibited pronounced excess of females in the Nepalese population.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was less compared to earlier studies where the prevalence of hearing loss in diabetes mellitus patients quoted from a range of 33.7% to 97.6%. [15][16][17][18][19] We did not find clarification for such a broad variation, but it could be attributed to the study methodology of differences in inclusion criteria, demographics, type and duration of diabetes mellitus, the clinical and biochemical status of diabetes mellitus patients. The current study did not limit the recruitment of study participants according to the duration of disease, age, or gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those characteristics will adversely affect the patient’s quality of life and their ability to live independently [8]. Also, considering that hearing impairment is associated with diabetes and that this is a major public health problem in low and middle-income countries and in developed economies, it is important to develop population-based studies in order to know the magnitude of this association.…”
Section: Introductionmentioning
confidence: 99%